The use of multimedia in the Childwatch International research network - Per Miljeteig; Marie Louse Bistrup (The Turkish Journal of Pediatrics)
The article describes the background and the activities in the Childwatch International research network In using electronic communication. The network has a core of 30 institutions world-wide that work together to establish Childwatch International as a tool for international cooperation and for mutual support in capacity enhancing within child research.